Design of a Reverse Osmosis–Based Seawater Desalination System Utilizing Coconut Shell - Mutia Amyranti; Bambang Andri Yoga; Ratih Kurniasari; Ismi Nurlatifah; Lily Arlianti; Siti Maftukhah; Dine Agustine (Asian Journal of Environmental Research, 2026)
Freshwater scarcity remains a critical challenge in small island regions, particularly in archipelagic countries such as Indonesia, where seawater is abundant but access to clean freshwater is limited. Tunda Island, located in Serang Regency, Banten Province, exemplifies this condition, as local communities primarily depend on rainwater harvesting and shallow groundwater sources to meet daily water demands. This study aims to evaluate a modified reverse osmosis (RO) desalination system integrated with coconut shell–based activated carbon as an adsorptive pretreatment medium for seawater desalination. The coconut shell adsorbent was employed to enhance pretreatment efficiency and improve the overall performance of the RO system. Seawater samples collected from Tunda Island were processed through the integrated system, and the quality of the treated water was evaluated according to the Indonesian Ministry of Health standards. Key parameters analyzed included Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Dissolved Solids (TDS), Total Suspended Solids (TSS), pH, color, and temperature. The results demonstrated that the treated water achieved COD of 120.10 mg/L, BOD of 10.5 mg/L, TSS of 3.76 mg/L, TDS of 117.245 ppm, pH of 7.30, clear color, and a temperature of 27°C, indicating compliance with applicable water quality standards. These findings confirm that the integration of coconut shell–based activated carbon with reverse osmosis effectively improves desalination performance and produces freshwater suitable for domestic use.